Analisis Tingkat Kepuasan Pelanggan Pencucian Mobil Atas Kinerja Pelayanan Pada CV. Jasa Raya Baru Semarang - Rahman, Dharma Arif; Lubis, Nawazirul; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
The development of car wash services for years to yeras are increasing and becoming on concern for the society. From the customer complains data in CV. Jasa Raya Baru Semarang from Juni to December 2013, there are complains such as the car is not well drained, lack of cleaness and the washing time is too long. This research aims to determine the level of car wash customer satisfaction in CV. Jasa Raya Baru Semarang. Viewed from the dimension of realibility, responsiveness, assurance, empathy, and physical evidence.The type research that is used is descriptive analysis. The data used in the research is the primary data obtained by using the instrumens of gathering data in the from of a questionnaire and question’s guidelines. The population in this research is all customers in 2013, 4025 samples are taken according to Donald R. Cooper aboute 100 respondens by using purposive sampling technique. Data analysis that is used in the research is important and performance analysis.On the basis of importance analysis, can be concluded that:The customers of car wash service in CV. Jasa Raya Baru Semarang are less satisfied with the dimension of reability.The customers of car wash service in CV. Jasa Raya Baru Semarang are less satisfied with the dimension of responsiveness.The customers of car wash service in CV. Jasa Raya Baru Semarang are less satisfied with the dimension of assurance.The customers of car wash service in CV. Jasa Raya Baru Semarang are less satisfied with the dimension of empathy.The customers of car wash service in CV. Jasa Raya Baru Semarang are less satisfied with the dimension of physical evidence.The average satisfaction level based on the importance and performance analysis is 3,55 (less satisfied). This indicates that respondens fell less satisfied with the services provided by car wash in CV. Jasa Raya Baru Semarang. In here are advices for car wash CV. Jasa Raya Baru Semarang: to improve the performance of the car wash services that are considered less attention from the company, such as, checking the car before it is about to be wash, easy costumers in establishing interaction with employes, employee’s capability in instealing a sence of trust to be customer, the company is having employes who are provided with the appropriate, field experinces with their work, giving attention regardless of the customers social status, the understanding of companys employees to understand the customers needs the company appreciating the customer’s time, the design of car wash place that interesting.